2002
DOI: 10.1128/mcb.22.13.4522-4534.2002
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Receptors Inhibit AP1 Activation by Regulating Extracellular Signal-Regulated Kinase and CBP Recruitment to an AP1-Responsive Promoter

Abstract: Retinoids exhibit antineoplastic activities that may be linked to retinoid receptor-mediated transrepression of activating protein 1 (AP1), a heterodimeric transcription factor composed of fos-and jun-related proteins. Here we show that transcriptional activation of an AP1-regulated gene through the mitogen-activated protein kinase (MAPK)-extracellular signal-regulated kinase (ERK) pathway (MAPK ERK ) is characterized, in intact cells, by a switch from a fra2-junD dimer to a junD-fosB dimer loading on its prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 51 publications
5
74
0
Order By: Relevance
“…7). Coactivators such as CBP were required for activation of RA-responsive genes, and inhibition of AP-1 activity by RA was attributed to RAR competition for limiting amounts of CBP (4,11). In the case of retinoic acid signaling, the displacement of coactivator binding occurs with faster kinetics than repressor dissociation from RAR␣.…”
Section: Discussionmentioning
confidence: 99%
“…7). Coactivators such as CBP were required for activation of RA-responsive genes, and inhibition of AP-1 activity by RA was attributed to RAR competition for limiting amounts of CBP (4,11). In the case of retinoic acid signaling, the displacement of coactivator binding occurs with faster kinetics than repressor dissociation from RAR␣.…”
Section: Discussionmentioning
confidence: 99%
“…This is accompanied by an increase in JunD-FosB binding and a decrease in JunD-Fra2 binding at the AP1 site (Benkoussa et al, 2002). Constitutively tethering RAR (all-trans retinoic acid receptor) to the promoter, together with treatment with atRA (all-trans retinoic acid) and TPA, led to decreased recruitment of ERKs, CBP and pol II (Benkoussa et al, 2002). It was therefore suggested that RAR might regulate ERK access to the AP1 complex and hence modulate phosphorylation of its substrate and CBP association (Benkoussa et al, 2002).…”
Section: Cyc8p Tup1pmentioning
confidence: 99%
“…Using ChIP assays, Benkoussa et al found that activation of ERKs by 12-O-tetradecanoylphorbol-13-acetate (TPA) leads to recruitment of ERK1 and ERK2, CREB-binding protein (CBP) and pol II to an AP1-responsive reporter gene in vivo (Benkoussa et al, 2002). This is accompanied by an increase in JunD-FosB binding and a decrease in JunD-Fra2 binding at the AP1 site (Benkoussa et al, 2002).…”
Section: Cyc8p Tup1pmentioning
confidence: 99%
See 2 more Smart Citations